2009
DOI: 10.1038/emboj.2009.193
|View full text |Cite
|
Sign up to set email alerts
|

MRE11–RAD50–NBS1 is a critical regulator of FANCD2 stability and function during DNA double-strand break repair

Abstract: Monoubiquitination of the Fanconi anaemia protein FANCD2 is a key event leading to repair of interstrand cross-links. It was reported earlier that FANCD2 co-localizes with NBS1. However, the functional connection between FANCD2 and MRE11 is poorly understood. In this study, we show that inhibition of MRE11, NBS1 or RAD50 leads to a destabilization of FANCD2. FANCD2 accumulated from mid-S to G2 phase within sites containing single-stranded DNA (ssDNA) intermediates, or at sites of DNA damage, such as those crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 64 publications
9
44
0
Order By: Relevance
“…45,50 CtIP or Mre11 appear to be involved in an early step in ICL repair, because CtIP or Mre11 depletion prevents FANCD2 recruitment to sites of damage and ubiquitylation of FANCD2 in the presence of ICL damage. 23,42 Since CtIP and Mre11 are implicated in resection just upstream of DNA2, 29,31,32,51 it was of interest to test whether DNA2 was also required at an early step for FANCD2 activation. Previously, we showed that the depletion of endogenous DNA2 did not affect FANCD2 monoubiquitination after cisplatin treatment.…”
Section: Over-resection Can Inhibit Crosslink-triggered Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…45,50 CtIP or Mre11 appear to be involved in an early step in ICL repair, because CtIP or Mre11 depletion prevents FANCD2 recruitment to sites of damage and ubiquitylation of FANCD2 in the presence of ICL damage. 23,42 Since CtIP and Mre11 are implicated in resection just upstream of DNA2, 29,31,32,51 it was of interest to test whether DNA2 was also required at an early step for FANCD2 activation. Previously, we showed that the depletion of endogenous DNA2 did not affect FANCD2 monoubiquitination after cisplatin treatment.…”
Section: Over-resection Can Inhibit Crosslink-triggered Repairmentioning
confidence: 99%
“…23 Thus, CtIP and MRN complex play a role early in the FA/BRCA pathway in addition to their critical role in the HDR step required for the completion of FA/BRCA repair. In summary, the interaction of FA/BRCA factors with so many additional DNA repair factors and pathways suggests that the FA pathway may be the central sensor and/or regulator for most cellular DNA damage responses.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that components of the MRN complex can also influence the stability of other proteins involved in DNA damage response. For example, MRN is an indispensable for stabilization of FANCD2 during DNA repair as silencing of MRN by the specific inhibitor Mirin influenced accumulation of FANCD2 at the sites of DNA DSBs [118].…”
Section: Mrn Is a Vital Dna Damage Complexmentioning
confidence: 99%
“…This suggests that BRCA1 and CtIP play a role downstream of the FA core complex allowing for FANCD2 foci formation at the site of damage. A role for the MRN complex in FANCD2 stability has also been reported as silencing of MRE11, RAD50 or NBS1 leads to decrease in FANCD2 protein life [74]. Together these data suggest that integral members of HRR are needed for proper FANCD2 function within the FA network.…”
Section: Prr Pathway Fa Network and Hrr Pathway Crosstalkmentioning
confidence: 72%